Plasma Interaction Signatures of Plumes at Europa. Issue 1 (13th January 2020) - Arnold, Hannes; Liuzzo, Lucas; Simon, Sven
Abstract: The goal of our study is to present a systematic modeling framework for the identification of water vapor plumes in plasma and magnetic field data from spacecraft flybys of Europa. In particular, we determine the degree to which different plume configurations can be obscured by the interaction of Jupiter's magnetospheric plasma with Europa's induced dipole field and its global atmosphere. We apply the hybrid model AIKEF (kinetic ions, fluid electrons) to investigate the effect of inhomogeneities in Europa's atmosphere (plumes) on the plasma interaction with the Jovian magnetosphere. To systematically assess the magnitude and structure of the perturbations associated with the plume‐plasma interaction at Europa, we vary the plume location across Europa's surface while considering different symmetric and asymmetric density profiles of the moon's global atmosphere. To isolate the impact of a plume on Europa's magnetospheric environment, we also conduct model runs without any global atmosphere. To quantify the magnetic perturbations caused by plumes, we analyze the field components along hypothetical spacecraft trajectories through each plume. Conclusions of our study are (1) localized regions of stagnant flow are most indicative of the presence of a plume. (2) The visibility of plumes in the magnetic field strongly depends on the density profile (whether it is symmetric or asymmetric) of the global atmosphere. (3) The presence of an induced dipole complicates the identification of magnetic signatures associated with a plume and dominates Europa's magnetic environment in its intermediate vicinity. (4) Complex fine structures are visible in the tail of escaping plume ions. Key Points: Localized regions of stagnant flow are most indicative of the presence of a plume at Europa The visibility of plumes in spacecraft data highly depends on the density profile of the global atmosphere and the presence of an induced dipole Precise knowledge of the plasma's upstream parameters is required to identify plumes in spacecraft data